Action research: A proposal for training and titration in the careers of Initial and Primary Education of a private higher education institution in Lima - Liza Cabrera Morgan (Educación, 2017)
The goal of this essay is to share the project proposal about the use of the action research approach in the degree completion award process for students in the Pre-school and Primary Education specialization in a private higher education institution of Lima. This is done within the framework of the implementation process for the new curriculum plan initiated in 2013. In that sense, we highlight the characteristics of this type of research that have been embodied in practice, the process followed for its application, as well as achievements, difficulties and the aspects that we still need to work out. Lastly, some thoughts are proposed to consolidate this type of research in the academic and organizational structure of this institution, which could prove useful for higher education institutions interested in the implementation of this research approach.